BORDER SECURITY AND TRANSNATIONAL THREATS: A COMPARATIVE ANALYSIS OF NIGERIA-NIGER BORDER DYNAMICS - MUHAMMAD SHEHU; ABDURASHID DALHA (International Studies Journal)
Border security is of utmost importance when it comes to safeguarding a nation's security and sovereignty against any possible threats. Its primary objective is to manage and regulate the movement of individuals across borders, thereby mitigating the illicit transport of goods and persons. The boundary that divides Nigeria and Niger, known for its expansive nature and lack of strict control, has become a central point for numerous cross-border threats, thus necessitating a thorough examination of its dynamics. This paper aims at making a comparative analysis of the security issues that both Nigeria and Niger share at the border, delving into the intricate network of transnational challenges and their implications for the well-being and safety of individuals in the region.The border that separates Nigeria and Niger has experienced a convergence of diverse issues, including terrorism, insurgent activities, drug and weapons smuggling, human trafficking, and criminal enterprises that operate across the border. This analysis also aims to clarify the complex and multidimensional nature of these challenges, by exploring the underlying factors and evaluating their significant impact on the lives and livelihoods of the communities residing in the borderlands.In doing this, the similarities and distinctions in the security dynamics of both nations, taking into account the geopolitical, cultural, and economic factors that exert influence upon these dynamics will be explored.